Functional Verification of Two Genes Related to Stripe Rust Resistance in the Wheat-Leymus mollis Introgression Line M8664-3 - Jin, Pengfei; Chao, Kaixiang; Li, Juan; Wang, Zihao; Cheng, Peng; Li, Qiang; Wang, Baotong (Frontiers in Plant Science, 2021)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most widespread and destructive fungal diseases on wheat worldwide. The cultivation and growth of resistant wheat varieties is the most economical, effective, and environmentally friendly method to control stripe rust. Therefore, it is necessary to use new resistance genes to breed resistant wheat varieties. A single dominant gene temporarily designated as YrM8664-3, from a wheat-Leymus mollis introgression line M8664-3 highly resistant to Chinese predominant Pst races, is a potentially valuable source of stripe rust resistance for breeding. Herein, based on the previous YrM8664-3 chromosome location results (bin 4AL13-0.59-0.66 close to 4AL12-0.43-0.59) and expression change information of candidate genes and bioinformatics analysis, several candidate genes with significantly different expression changes were then selected and verified by virus-induced gene silencing (VIGS). Two of the candidate genes temporarily designated as TaFBN (contain PAP_fibrillin domain in its protein) and Ta_Pes_BRCT (contain Pescadillo and BRCT domain in its protein), produced the most significant resistance changes in the wheat-Pst interaction system after silencing. These two genes were further verified by Agrobacterium-mediated wheat genetic transformation technology. According to the identification of disease resistance, the resistance function of the candidate gene TaFBN was further verified. Then, the expression of TaFBN under hormone treatment indicated that TaFBN may be related to the salicylic acid (SA) and abscisic acid (ABA) signaling pathways. Combined with the expression of TaFBN in response to environmental stress stimulation, it can be reasonably speculated that TaFBN plays an important role in wheat to Pst resistance and involves in abiotic stress pathways.